FRI0313 Body Mass Does not Affect Clinical Outcomes of Therapy with Abatacept in Rheumatoid Arthritis (RA) Patients. A Pan-European Analysis of RA Registries. (10th June 2014) - Iannone, F.; Finckh, A.; Neto, D.; Gomez-Reino, J.; Lie, E.; Canhão, H.; Pavelka, K.; Turesson, C.; Mariette, X.; Gottenberg, J.-E.; Hetland, M.
Abstract : Background: Obesity is becoming an emerging issue in the treatment of rheumatic diseases and body mass index (BMI) has been reported to affect both the disease activity and the clinical response to anti-TNF drugs (1, 2). However, until now there has been no specific data on drugs other than TNF inhibitors in obese patients with RA. Objectives: To assess whether BMI has impact on drug survival and response of Abatacept (ABA) in RA patients treated in clinical practice across Europe. Methods: We analysed longitudinal prospective data from 8 different European registries of RA patients starting treatment with ABA in the routine care settings. Aim of the study was to evaluate the influence of obesity on drug adherence and LUNDEX-EULAR good or moderate response rates to ABA and to search for possible predictors of drug discontinuation. LUNDEX-EULAR good response rates were calculated as the fraction of patients adhering to therapy multiplied by the fraction of patients achieving EULAR good response at 1 year. According to WHO classification, patients were stratified as underweight (BMI <18.5), normal weight (BMI 18.5 – 24.99), overweight (BMI 25.00 – 29.99), and obese (BMI >30.00). Time to discontinuation was defined as the span between drug initiation and last administered dose plus one dispensation interval. Kaplan-Meier life table method was used to estimate drug adherence and Cox regression to estimate hazard ratios (HRs) for discontinuation. Predictors of discontinuation were investigated using multivariable models, with gender, disease activity, age, BMI as continuous variable, BMI WHO class, and number of previous biologics. Results: BMI was available for 785 out of 3821 patients on ABA therapy. We identified 31 underweight, 350 normal-weight, 249 overweight and 155 obese patients. Age, disease duration, number of previous biologics, baseline function (HAQ) and disease activity (DAS28) did not differ between groups. The proportion of male patients was significantly higher among overweight (26%) than in obese (15%) or normal-weight (13%) patients, (p<0.001). The distribution of BMI was similar among the 8 registries. Drug discontinuation rates were similar in all weight groups (HR for obese: 0.91 (95%CI: 0.68-1.24), for overweight: 1.17 (95%CI: 0.90-1.51). At 4-years, ABA survival rates were 37% in normal-weight, 39% in overweight and 40% in obese patients (p=0.07). Furthermore, 1-year LUNDEX-EULAR good or moderate responses were also comparable: 59% in normal-weight, 59% in overweight and 67% in obese patients (p=0.45). There was no statistically significant association between ABA discontinuation and BMI as continuous variable, nor effect modification by autoimmunity status (RF and/or ACPA antibodies). Conclusions: In this study of 785 patients with RA treated with ABA across Europe we did not find an effect of BMI on clinical outcomes unlike what has previously been shown for TNF-inhibitors. References: Klaasen R. et al. Arthrits Rheum 2011;63:359-64. Gremese E. et al. Arthritis Care Res 2013;65:94-100 Disclosure of Interest: F. Iannone: None declared, A. Finckh Grant/research support: Unrestricted Research grant from BMSD, D. Neto Grant/research support: Unrestricted Research grant from BMSD, J. Gomez-Reino: None declared, E. Lie: None declared, H. Canhão: None declared, K. Pavelka: None declared, C. Turesson: None declared, X. Mariette: None declared, J.-E. Gottenberg: None declared, M. Hetland: None declared DOI: 10.1136/annrheumdis-2014-eular.5630